Global Trends in Nursing-Related Research on COVID-19: A Bibliometric Analysis - Zhang, Qian; Li, Shenmei; Liu, Jing; Chen, Jia (Frontiers in Public Health, 2022)
Background Coronavirus disease 2019 (COVID-19) has significantly impacted healthcare, especially the nursing field. This study aims to explore the current status and hot topics of nursing-related research on COVID-19 using bibliometric analysis. Methods Between 2019 and 2022, publications regarding nursing and COVID-19 were retrieved from the Web of Science core collection. We conducted an advanced search using the following search query string: TS = (“Novel coronavirus 2019” or “Coronavirus disease 2019” or “COVID 19” or “2019-nCOV” or “SARS-CoV-2” or “coronavirus-2”) and TS = (“nursing” or “nurse” or “nursing-care” or “midwife”). Bibliometric parameters were extracted, and Microsoft Excel 2010 and VOSviewer were utilized to identify the largest contributors, including prolific authors, institutions, countries, and journals. VOSviewer and CiteSpace were used to analyze the knowledge network, collaborative maps, hotspots, and trends in this field. Results A total of 5,267 papers were published between 2020 and 2022. The findings are as follows: the USA, China, and the UK are the top three prolific countries; the University of Toronto, the Harvard Medical School, the Johns Hopkins University, and the Huazhong University of Science & Technology are the top four most productive institutions; Gravenstein, Stefan, and White, Elizabeth M. from Brown University (USA) are the most prolific authors; The International Journal of Environmental Research and Public Health is the most productive journal; “COVID-19,” “SARS-CoV-2,” “nurse,” “mental health,” “nursing home,” “nursing education,” “telemedicine,” “vaccine-related issues” are the central topics in the past 2 years. Conclusion Nursing-related research on COVID-19 has gained considerable attention worldwide. In 2020, the major hot topics included “SARS-CoV-2,” “knowledge,” “information teaching,” “mental health,” “psychological problems,” and “nursing home.” In 2021 and 2022, researchers were also interested in topics such as “nursing students,” “telemedicine,” and “vaccine-related issues,” which require further investigation.